Strategi Jabar Saber Hoaks Sebagai Media Klarifikasi Hoaks Melalui Pengelolaan Konten Pada Media Sosial Instagram @jabarsaberhoaks - Fadjriah, Mutiaranisa Nur; Damayanti, Trie (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this research is to find out how Jabar Saber Hoaks strategy in delivering hoax clarification information as Jabar Saber Hoaks work program, and how Jabar Saber Hoaks work program is related to content management on Instagram social media @jabarsaberhoaks with the scope of public relations work. This research method uses an exploratory research method which is a study that aims to collect data to answer problems that are of interest to researchers. Exploratory research conducts exploration or introduction to certain research symptoms. The activity carried out by Jabar Saber Hoaks is the management of infographic content which is then upgraded to short video content uploaded on Instagram social media @ Jabarsaberhoaks through the hoax media monitoring process, fact check, content packaging, and content publication to the official Instagram @jabarsaberhoaks. Jabar Saber Hoaks' objectives are in line with the objectives of public relations according to the dictionary published by the Institute of Public Relations (IPR), namely to ensure that the goodwill and progress of the agency concerned are always understood by its public, and Jabar Saber Hoaks also carries out its work program in terms of communication of hoax information in a planned and sustainable manner. Public Relations must be able to adapt and blend with technological developments, in line with Jabar Saber Hoaks which seeks to adapt to technological developments, by developing its form of communication from only clarifying information in the form of infographic content to developing clarifying information packaged in the form of short video content, and then uploaded via Instagram social media @jabarsaberhoaks.